2019
DOI: 10.1177/1971400919861409
|View full text |Cite
|
Sign up to set email alerts
|

Early assessment of recurrent glioblastoma response to bevacizumab treatment by diffusional kurtosis imaging: a preliminary report

Abstract: Purpose The purpose of this preliminary study is to apply diffusional kurtosis imaging to assess the early response of recurrent glioblastoma to bevacizumab treatment. Methods This prospective cohort study included 10 patients who had been diagnosed with recurrent glioblastoma and scheduled to receive bevacizumab treatment. Diffusional kurtosis images were obtained from all the patients 0–7 days before (pre-bevacizumab) and 28 days after (post-bevacizumab) initiating bevacizumab treatment. The mean, 10th, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 76 publications
0
1
0
Order By: Relevance
“…Recently, Grossmann et al [ 80 ] reported that radiomics provide prognostic value for survival and progression of patients with GBM receiving BEV treatment. In addition, Lee et al [ 81 ] demonstrated that diffusional kurtosis imaging, which is an extension of diffuse tensor imaging, allows the detection of tissue changes 28 days after initiating BEV treatment and may provide information regarding tumor progression.…”
Section: Predictive Markers Of Bevmentioning
confidence: 99%
“…Recently, Grossmann et al [ 80 ] reported that radiomics provide prognostic value for survival and progression of patients with GBM receiving BEV treatment. In addition, Lee et al [ 81 ] demonstrated that diffusional kurtosis imaging, which is an extension of diffuse tensor imaging, allows the detection of tissue changes 28 days after initiating BEV treatment and may provide information regarding tumor progression.…”
Section: Predictive Markers Of Bevmentioning
confidence: 99%